Evaluation of the Discrepancy Model in the Implementation of Consultation Services - Siti Nurhaliza; Nur Hidayah; Fitri Wahyuni; Abi Fa'izzarahman Prabawa; Syahira Alfikriah; Afifah Army Age (Indonesian Journal of Counseling and Development, 2026)
Consultation services are a critical component of school guidance, requiring systematic evaluation to ensure quality and accountability. This study evaluated the implementation of consultation services at SMA Negeri Taruna Nala, East Java, using Provus’s (1971) Discrepancy Evaluation Model. A mixed-methods design was employed; quantitative data were collected via a 100-item instrument using a 1–7 Likert scale, while qualitative data were gathered through unstructured interviews. The subject was one school counselor with 20 years of professional experience. The baseline standard applied was Standard 3, Criterion 6 of ABKIN, adopted from the South Carolina Guidance and Counseling Program Model. The results revealed a total score of 679 out of 700 (97.00%), indicating full implementation. Aspect-level analysis showed high implementation across dimensions: Organization (97.86%), Planning (95.71%), Design (100%), Implementation (98.57%), and Evaluation (92.86%). Notably, item 24 (selective planning) scored 1, demonstrating that establishing written criteria for cases requiring formal consultation remains a key area for improvement. Item 71 (principal involvement) scored 5, indicating partial implementation, while ten items in the Evaluation aspect scored 6, highlighting opportunities to strengthen evaluation through systematic standardization. As a single-case evaluation, these findings describe the practices of one counselor and cannot be generalized to broader institutional services. Additionally, the evaluation relied solely on the counselor's self-reports without integrating perspectives from other stakeholders, such as the principal, homeroom teachers, or parents